Al-Musykilāt aṣ-Ṣauṭiyah ladā ad-Dāris bigair al-‘Arabiyyah ‘inda Ta’allum Mahārah at-Tahadduṡ - Amar Faryat (IAIN Salatiga, 2022)
The study aimed to identify the phonemic issues that non-Arabic speakers encounter when learning speaking skills. Through collecting linguistic samples, the researchers discovered that the problems related to the phonemic system are among the deepest and the greatest problems in learning the speaking skills. Accordingly, it was necessary to analyze the linguistic level (the phonetic level) for learners of Arabic as a second language, in order to identify the most important problems of the sound system and propose some appropriate solutions. This study used the descriptive analytical method, and relied on interviews via modern technology means like Skype. It was determined that some Arabic sounds are difficult for learners to pronounce. The study's findings led to several recommendations, the most important of which is the requirement that Arabic linguistic sounds be taught to non-native speakers using a graduated system that progresses from easy to difficult. That is, it is necessary to first teach the consonant sounds (baa, taa, jim, thaal, dal, ra, zai, sein, shin, kaf, lam, mim and nun), and put them in easy meaningful words, then teach the emphatic sounds (sad, daad, ta’ and tha’) and use them in a concrete context. After that move to teaching the laryngeal sounds (hamza, haa, aain, ghain, Ha, Xa and qaf), and incorporate them into words that are easy to pronounce. Finally, present the vowels, emphasizing how long and short vowels differ from one another.